Revision of the brief international classification of functioning, disability and health core set for multiple sclerosis: a study of the comprehensive icf core set for multiple sclerosis with participants referred for work ability assessment - Daiva Valadkevičienė; Dalius Jatužis; Irena Žukauskaitė; Virginija Danylaitė Karrenbauer; Indre Bileviciute-Ljungar (Journal of Rehabilitation Medicine, 2024)
Objective: To evaluate the Comprehensive International Classification of Functioning, Disability and Health (ICF) Core Set for multiple sclerosis with regard to the Brief ICF Core Set for multiple sclerosis.